Hubungan Budaya Korean Terhadap Karakter Siswa di SMP N 1 Kecamatan Payakumbuh - ‘Aisyi, Asqia Rahadatul; J, Januar (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research is titled “The Relationship Between Korean  and Student Character at SMP N 1 Kecamatan Payakumbuh,” written by Asqia Rahadatul ‘Aisyi, Student ID 2120163, Islamic Religious Education Study Program, Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri (UIN) Sjech M. Djamil Djambek Bukittinggi. 2024. One of the foreign cultures influencing student character is pop culture, which comprises cultural elements that gain widespread popularity among the public. This includes music, films, fashion, and other trends that are generally accepted and consumed by many people. Pop culture often reflects mass tastes and preferences and can change over time. Pop culture forms a vortex and current with values that influence society in various ways. This study aims to examine the Relationship Between Korean Pop Culture and Student Character at SMP N 1 Kecamatan Payakumbuh. The population in this study consists of students from class VIII-2 of SMP N 1 Kecamatan Payakumbuh. This is a quantitative study using purposive sampling technique with a sample size of 32 individuals. The primary data source is derived from questionnaires distributed to the students. Data analysis uses simple regression. Student character is the dependent variable, and Korean pop culture is the independent variable. The results of this study show that: (1) there is a relationship between Korean pop culture and student character, where many students imitate Korean clothing, hairstyles, and language. (2) Korean pop culture has a significant and positive influence on student character, with t_calculated > t_table, namely (3.308 > 2.042) (sig 0.002 < 0.05), thus the hypothesis is accepted. Therefore, the variable of student character at SMP N 1 Kecamatan Payakumbuh is related to Korean pop culture (K-pop). This means that the greater the affinity towards Korean pop culture (K-pop), the more it changes a student's character at SMP N 1 Kecamatan Payakumbuh.